PENGARUH FINANCIAL TECHNOLOGY TERHADAP KEPUASAN KEUANGAN DENGAN CAPAIAN KEUANGAN SEBAGAI VARIABEL MEDIASI - Pristin Prima Sari; Risal Rinofah (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2019)
This study aims to investigate the mediation role of financial experience on the link between financial technology and financial satisfaction of Small Business Enterprise (SME) in Beringharjo Market in Yogyakarta. This study uses primary data and random sampling. This Study uses questionairre with likert scale. This study collects data to respondent in Beringharjo Market of Yogyakarta Special Region. The results of the study are the F test showing that financial performance can mediate the effect of using financial technology on financial satisfaction. Financial technology can improve the financial performance of small businesses and financial achievements can increase the financial satisfaction of small businesses in Beringharjo market. Thus, financial performance can mediate the influence of Financial Technology on financial satisfaction. The criteria for the role of mediation in financial performance are fully mediated, meaning that financial performance partial mediated the relationship between financial technology and financial satisfaction. This study can be used to campaign fianncial technology to small busniess entreprise (SME), to develop small business entreprise (SME), to make decision in business especially small business entreprise (SME).